IMPLEMENTASI TEKNOLOGI DALAM MAHARATUL ISTIMA' DI LINGKUNGAN MADRASAH DINIYAH AR-RIDHO (JOMBANG) - Mubasyiroh, Abila Al; Ulin Nuha’, Muhammad Afthon (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2025)
This study aims to examine the application of technology in the learning process of maharotul Istima' (listening ability) in students at Madrasah Diniyah which is under the auspices of the Ar-ridho Foundation. This research will explain in detail the steps of how technology is applied in the madrasah, as well as how it affects the improvement of students' listening skills. Thus, it is hoped that this research can provide insight into the effectiveness of the use of technology in supporting the learning process in madrasas, especially in improving students' maharotul Istima' abilities. In this study, a descriptive qualitative method is used by sorting them according to certain categories, describing the data obtained from interviews and observations. The results of this study show that the process of implementing technology in learning Mahārat al-Istimā' at Madrasah Diniyah Ar-Ridho involves needs analysis, provision of basic technology, infrastructure improvement, teacher training, integration of modern methods, annual evaluation and continuous adaptation. This allows for gradual and significant technological advancements, thus supporting effective listening learning.